THE IMPLEMENTATION OF MAP-DRAWING AS A MEDIA TO TEACH LISTENING SKILL OF RECOUNT TEXTS TO THE TENTH GRADERS IN MA. ROUDLOTUL BANAT SIDOARJO (RETAIN, 2015)
Abstract This study deals with the implementation of map-drawing to teach listening skill to the tenth graders. Based on the curriculum of 2013, listening of recount text is re-taught in the tenth grade. Here, the teacher is supposed to conduct listening activity of recount texts in this grade. However, the implementation of listening is sometimes neglected by some teachers. Besides, the students show a little interest in listening activity because of the task was boring. Furthermore, some students get difficulty gaining the information of the listening audio/task because they are busy with their long notes. As the result, they get a very little information, and they cannot do the task perfectly. This problem can be overcome by bringing a media, which is map-drawing. It is a media which presents incomplete map with pictures. The students’ job is to draw the lines from one place to others and put the numbers of the pictures which represent the story. In this study, the writer would like to describe the implementation of map-drawing as a media to teach listening skill of recount texts and students’ attitudes toward the implementation of this media. This study used descriptive qualitative design. The subjects chosen were the students of the tenth grade of MIA/IPA of MA. Roudlotul Banat. The observations were conducted twice. The writer used observation checklists and questionnaire to gain the data of the map-drawing implementation and students’ attitudes. The data of observation checklists were taken when the teaching-learning was conducted, and the questionnaires were given to the students after the program. From the results, the writer concluded that map-drawing could help the student do the listening activities of recount texts, because it released the students’ burdens while having listening practice by providing pictures and numbers. Besides the pictures and numbers could interest the students, so that they could do the task better. Moreover, the students also gave positive attitudes towards the implementation of map-drawing. It could be seen from the students’ ability in answering the teacher’s questions both orally and written. Key Words: Listening, Media, Map-drawing. Abstrak Penelitian ini berhubungan dengan penerapan media map-drawing dalam pengajaran listening recount teks untuk kelas x. Berdasarkan kurikulum 2013, mendengar teks recount kembali diajarkan pada kelas x. Disini, guru diharapkan untuk menerapkan latihan mendengar teks recount pada level ini. Tetapi kenyataannya praktik mendengar sering sekali diabaikan oleh guru karena latihan mendengar kurang dianggap penting. Disamping itu, siswa terkadang merasa bosan dengan pelajaran listening yang terkesan kurang menarik. Siswa juga sering kesulitan dalam menangkap informasi yang terkandung dalam audio atau teks yang dibacakan. Hal ini disebabkan karena kebanyakan siswa terlalu sibuk menulis semua apa yang mereka dengar yang pada akhirnya mereka kehilanggan informasi yang seharusnya mereka dapat, dan mereka tidak dapat mengerjakan soal mendengar dengan baik. Akan tetapi masalah ini dapat ditangani dengan menggunakan media map-drawing. Map-drawing sendiri berupa map yang berisi gambar. Tugas siswa disini adalah menggambar garis dri satu tempat ke tempat lain dan menomori lingkaran yang tersedia dengan angka pada gambar sesuai dengan ceritta. Dalam penelitian ini, penulis akan menggambarkan penerapan media map-drawing dalam mendengar teks recount untuk kelas X. Disamping itu, penulis juga akan mendiskripsikan hasil dari sikap siswa terhadap penerapan media ini. Penelitian ini menggunakan metode deskripsi kualitatif. Subjek yang dipilih untuk penelitihan ini adalah siswa-siswa kelas X MIA di MA. Roudlotul Banat. Penelitian dilaksanakan selama dua kali. Disamping itu, penulis menggunakan observasi ceklis dan kuesioner untuk mendapatkan data penerapan media map-drawing dan sikap siswa. Data dari observasi ceklis diambil ketika proses belajar-mengajar berlangsung, dan kuesioner dibagikan setelah proses belajar-mengajar. Dari hasil penelitian ini, penulis menyimpulkan bahwa map-drawing dapat membantu siswa dalam mengerjakan tugas mendengar teks recount, karena media ini dapat melepaskan sedikit beban pada siswa karena map-drawing berisi gambar dan angka. Gambar dan angka juga dapat membantu siswa tertarik terhadap praktik mendengar sehingga mereka dapat mengerjakannya dengan baik. Disamping itu, siswa juga menunjukkan sikap yang positif terhadap penerapan map-drawing. Hal ini dapat dilihat dari kemampusan siswa dalam menjawab pertanyaan guru secara lisan dan tertulis. Kata Kunci: Mendengar, Media, Map-drawing.